Mission in the early church themes and reflections - Smither, Edward L. (Cambridge, U.K. : James Clarke & Co, 2014)
The aim of this book is to begin a discussion about early Christian mission that will impact how we think about and approach mission today. To facilitate this, each chapter includes a relevant passage of Scripture as well as reflections where connections between early church and contemporary church practice can be made. Each chapter closes with some questions for reflection-points that will facilitate dialogue with Scripture and early church practice as the present global church moves forward in mission.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Missions -- History -- Early church, approximately 30-600.; Church history -- Primitive and early church, approximately 30-600.; RELIGION -- Christian Ministry -- Missions; Church history; Missions; RELIGION / Christian Ministry / Missions; Electronic books; History